Some indigenous methods of fish capture in Laguna de Bay - Elomina, Ambrosio A. (Miagao,Iloilo College of Fisheries, University of the Philippines, 1953)
In the Philippines one eats fish because it is the cheapest source of animal protein and phosphorus that are necessary for the proper growth and development of the body. One who observes the different methods of fish capture in the Philippines, particularly Laguna de Bay, realizes its significant contributions to our national economy. Before the outbreak of the Second World War, Japanese fishermen flock over the country and engage themselves in the exploitation of our natural resources, thereby producing fish in large quantities. Our small craft fishermen persist with their crude method and satisfy themselves with little income. At present the importance of our fishing industry has been fully realized. Many capitalists are engaging themselves or herself in commercial fishing all over the country. They prosper in the business and get a lot of profit by employing the proper technique of modern fishing methods. Production of fish now bolsters in many directions and the government gets its corresponding share. Still this practice will continue, time will come when there will be no supply of fish to meet the demand of inhabitants. The government now is trying her best to eliminate such practice, by employing coast guards, customs and naval patrols to protect our water for the purpose of fish conservation. In order to assure the citizenry and conserve our fishery, the people must be well informed of the legal fishing methods and good fishing. Laguna de Bay is one fishing ground in the Philippines they ought to know because it is of great value to the people residing near and also people in nearby places.
Keywords: Fish capture